Edukasi Pengelolaan Sampah Domestik dalam Mewujudkan Kampung Hijau Mandiri di RT 01 RW 06 Kelurahan Kreo Tangerang - Madonna, Sandra; Nursetyowati, Prismita; Dewi Meilasari Sugiana, Astrid; Djuitaningsih, Tita (Indonesian Journal for Social Responsibility, 2020)
Kampung Hijau Mandiri is one of Tangerang Government’s Programs to increase public awareness for a clean, green, and beautiful surrounding. Ninety-eight of Kampung Hijau Mandiri were formed throughout Tangerang’s Sub-Districts, one of which is in RT 01 RW 06, Kreo Sub-District. Criteria for Kampung Hijau Mandiri include a lively, comfortable and clean village with waste sorting initiatives. Kreo, one of the densely populated villages in Tangerang, has 22,837 inhabitants. Waste generated in RT 01 RW 06, Kreo, Tangerang is around 2,040 liters/day, quite large and can be reduced. Presently, household wastes in RT 01 RW 06 are still managed conventionally using the collection and disposal system. The economic potential of household organic and inorganic waste has not been optimally utilized. Organic waste management through composting (Takakura baskets) and non-organic waste management through waste banks are considered appropriate for processing household wastes. Hence, the community develops a new habit of sorting and processing waste into productive means, reducing waste generation transported to landfills. The waste management educational mentoring program was attended by 14 people, especially housewives and Posyandu cadres, through presentations and question and answer. This activity has great potential to endure as housewives and Posyandu cadres in RT 01 RW 06 Kreo Sub-District are influential household stakeholders in their environment. Residents of RT 01 RW 06 Kreo Sub-District agreed to initiate waste bank establishments. This program is expected to increase citizen’s involvement in waste management. RT 01 RW 06 Kreo is an exemplary Kampung Hijau Mandiri.